Congenital Absence of Right Coronary Artery without any other Associated Anomalies - A Case Report - Taimur, Syed Dawood Md; Khan, Saidur Rahman; Haq, M Maksumul; Mansur, Mahbub; Haque, Md Harisul; Sultan, Md Ashraf Uddin (University Heart Journal, 2011)
A 54 years gentleman presented with central compressive type of chest pain. He was newly diagnosed diabetic, dyslipidaemic. His ECG (electrocardiogram) showed features of anterior and inferior wall ischemia. Echocardiography revealed presence of regional wall motion abnormality. Exercise tolerance test was positive for provocable myocardial ischemia. Angiographic findings includes single coronary artery with congenital absence of RCA (Right coronary artery). Right coronary arterial territory was supplied by the terminal part of left circumflex coronary artery. Key Words: Congenital coronary; Right coronary artery (RCA); Single Coronary Artery. DOI: 10.3329/uhj.v6i1.7195 University Heart Journal Vol.6(1) 2010 pp.45-47